ACTA2 mutation with childhood cardiovascular, autonomic and brain anomalies and severe outcome. Issue 6 (23rd April 2013) - Meuwissen, Marije E.C.; Lequin, Maarten H.; Bindels‐de Heus, Karen; Bruggenwirth, Hennie T.; Knapen, Maarten F.C.M.; Dalinghaus, Michiel; de Coo, René; van Bever, Yolande; Winkelman, Beerend H.J.; Mancini, Grazia M.S.
Abstract Thoracic aortic aneurysm and dissection (TAAD) are associated with connective tissue disorders like Marfan syndrome and Loeys–Dietz syndrome, caused by mutations in the fibrillin‐1, the TGFβ‐receptor 1‐ and ‐2 genes, the SMAD3 and TGFβ2 genes, but have also been ascribed to ACTA2 gene mutations in adults, spread throughout the gene. We report on a novel de novo c.535C > T in exon 6 leading to p.R179C aminoacid substitution in ACTA2 in a toddler girl with primary pulmonary hypertension, persistent ductus arteriosus, extensive cerebral white matter lesions, fixed dilated pupils, intestinal malrotation, and hypotonic bladder. Recently, de novo ACTA2 R179H substitutions have been associated with a similar phenotype and additional cerebral developmental defects including underdeveloped corpus callosum and vermis hypoplasia in a single patient. The patient here shows previously undescribed abnormal lobulation of the frontal lobes and position of the gyrus cinguli and rostral dysplasis of the corpus callosum; she died at the age of 3 years during surgery due to vascular fragility and rupture of the ductus arteriosus. Altogether these observations support a role of ACTA2 in brain development, especially related to the arginine at position 179. Although all previously reported patients with R179H substitution successfully underwent the same surgery at younger ages, the severe outcome of our patient warns against the devastating effects of the R179C substitution on vasculature. © 2013 Wiley Periodicals, Inc.